2005
DOI: 10.1158/0008-5472.can-05-1069
|View full text |Cite
|
Sign up to set email alerts
|

High-level Coexpression of JAG1 and NOTCH1 Is Observed in Human Breast Cancer and Is Associated with Poor Overall Survival

Abstract: Aberrant activation of Notch receptors has been shown to cause mammary tumors in mice. We therefore used in situ hybridization to analyze expression of Notch ligands and receptors in human breast cancer. High levels of JAG1 and NOTCH1 were noted in a subset of tumors with poor prognosis pathologic features (P < 0.05). We therefore used tissue microarrays to analyze the expression of these genes in a collection of breast cancers from patients representing a wide spectrum of clinical stages, and from whom associ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
569
2
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 696 publications
(622 citation statements)
references
References 42 publications
31
569
2
7
Order By: Relevance
“…Jagged-1 has been found to be up-regulated in prostate 11 and some other cancers such as glioma and breast cancer. 14,15 Surprisingly, in the current study, we found that the knockdown of Jagged-1 exerts a much stronger growth inhibitory effect on prostate cancer cells compared to Notch-1 knockdown. This could be due to down-regulation of Jagged-1 along downregulation of the activity of other Notch family members, such as Notch-2.…”
Section: Discussioncontrasting
confidence: 59%
“…Jagged-1 has been found to be up-regulated in prostate 11 and some other cancers such as glioma and breast cancer. 14,15 Surprisingly, in the current study, we found that the knockdown of Jagged-1 exerts a much stronger growth inhibitory effect on prostate cancer cells compared to Notch-1 knockdown. This could be due to down-regulation of Jagged-1 along downregulation of the activity of other Notch family members, such as Notch-2.…”
Section: Discussioncontrasting
confidence: 59%
“…S8). Overexpression of Notch receptors and ligands and consequent increase in Notch activity has been reported in number of cancers, particularly the breast cancer and their early precursors, linking upregulated Notch signaling to pathogenesis (15,43,46). Therefore, several attempts have been made to inhibit Notch function by small-molecular inhibitors such as GSIs or short interfering RNAmediated approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that Notch receptor and ligands are overexpressed in the breast cancer tissues compared with the normal breast epithelium (14,27,43,44) and there is a strong correlation between high expression of Notch1 and Jagged1 and poor prognosis and survival (15). Because mAb 602.101 inhibited Jagged1 and Delta-like4 activities in the Notch1-overexpressing cells, ability of this antibody to inhibit Notch signaling in the cancer cell lines MCF-7 and MDA-MB-231 was investigated.…”
Section: Inhibition Of Notch Signaling In Breast Cancer Cell Lines Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Reedijk et al(2005) found that the expression of each member of the Notch gene family could be detected to varying degrees in a survey of 184 breast carcinomas. In fact, high levels of Notch1 and its ligand JAG1 were linked to poor overall survival.…”
Section: Discussionmentioning
confidence: 99%